Enhancing Effectiveness of Farm School through Community Wall Magazine (CWM): A Field Experimental Study (Indian Journal of Extension Education, 2023)
A field experimental study was conducted in Aligarh District of Uttar Pradesh to assess the feasibility of enhancing the effectiveness of Farm Schools (FS) through Community Wall Magazine (CWM). Four treatments with two replications were taken in the study. Treatments were information sharing through CWM (T1), information sharing through FS (T2) and supporting information sharing through FS with CWM (T3). Treatment T0 was taken to eliminate the effect of extraneous variables. Before and after treatment score of gain in the knowledge level of farmers regarding paddy cultivation practices was measured with the help of a knowledge test developed for the study. Matching in terms of the general profile of the farmers under all the replications was ensured before exposure to the treatments. Total farmers under the study were 200. Through CWM 21.83 per cent enhancement in knowledge level regarding rice cultivation practices of the farmers was observed. Due to the effect of FS on rice, 47.18 per cent enhancement in knowledge level was observed. The FS on rice which were supported with the information sharing through CWM 61.02 per cent enhancement in the knowledge level of beneficiary farmers was observed.